2020
DOI: 10.1182/bloodadvances.2020003458
|View full text |Cite
|
Sign up to set email alerts
|

Polarized mitochondria as guardians of NK cell fitness

Abstract: Distinct metabolic demands accompany lymphocyte differentiation into short-lived effector and long-lived memory cells. How bioenergetics processes are structured in innate natural killer (NK) cells remains unclear. We demonstrate that circulating human CD56Dim (NKDim) cells have fused mitochondria and enhanced metabolism compared with CD56Br (NKBr) cells. Upon activation, these 2 subsets showed a dichotomous response, with further mitochondrial potentiation in NKBr cells vs paradoxical mitochondrial fission an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 47 publications
1
49
1
Order By: Relevance
“…CD56 bright NK cells are the major producers of cytokines including IFN-γ (interferon-γ) and TNF-α (tumour necrosis factor-α), while CD56 dim NK cells primed for cytotoxicity with high expression of the cytotoxic machinery. CD56 dim NK cells purified directly from human peripheral blood mononuclear cells (PBMC) at steady state have higher rates of glycolysis and OXPHOS and increased mitochondrial mass when compared to CD56 bright NK cells [ 9 ]. There is also some evidence that human NK cells from blood and tissues such as the spleen and liver have different metabolic profiles [ 11 ].…”
Section: Metabolism Supporting Nk Cell Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…CD56 bright NK cells are the major producers of cytokines including IFN-γ (interferon-γ) and TNF-α (tumour necrosis factor-α), while CD56 dim NK cells primed for cytotoxicity with high expression of the cytotoxic machinery. CD56 dim NK cells purified directly from human peripheral blood mononuclear cells (PBMC) at steady state have higher rates of glycolysis and OXPHOS and increased mitochondrial mass when compared to CD56 bright NK cells [ 9 ]. There is also some evidence that human NK cells from blood and tissues such as the spleen and liver have different metabolic profiles [ 11 ].…”
Section: Metabolism Supporting Nk Cell Responsesmentioning
confidence: 99%
“…Various combinations of cytokines upregulate glycolysis and OXPHOS in murine NK cells that are accompanied by increased expression of key nutrient transporters, glycolytic enzymes, increased mitochondrial mass and metabolic fluxes [ 12 15 ]. Similarly, in human NK cells isolated from PBMC, 18-h stimulation with cytokines including IL2, IL12+IL15 or IL12+IL15+IL18 results in increased expression of nutrient receptor expression and enhanced glycolytic flux [ 9 , 16 ]. More recently, studies have shown IL-21 expanded human NK cells have significantly elevated basal and maximal glycolysis but downregulated OXPHOS compared to peripheral blood NK cells.…”
Section: Metabolism Supporting Nk Cell Responsesmentioning
confidence: 99%
See 3 more Smart Citations